Addition and multiplication of probabilities - Kamalova Xillolakhan Solijonovna (Global Scientific Publishing, 2024)
This article explores the fundamental concepts of probability, focusing on the addition and multiplication rules. It provides a comprehensive overview, including an introduction to probability theory, a literature review, detailed explanations of the methods used to apply these rules, and a discussion of their practical applications. The article concludes with key insights and suggestions for further study
Keywords: Probability theory; addition rule; multiplication rule